The reception of Ortega y Gasset’s thoughts in the work of Olivér Brachfeld - Ibarz Serrat, Virgili (2018)
In 1931, Olivér Brachfeld interviewed Ortega y Gasset for the Internationale Zeitschrift für Individual-Psychologie magazine. His book, Inferiority feelings, was published in 1936. In this article, we analyze the reception of Ortega y Gasset’s thoughts through the successive editions of Brachfeld’s work. Brachfeld argues that Ortega y Gasset establishes the foundations for a behavior analysis grounded on the feelings of self-esteem, and formulates a theory of inferiority feelings. Ortega y Gasset claims that arrogance results from a reaction, a diminution of our being, and explains it when he states that our spirit revolts and rebels against a reality that destroys our self-esteem. For Ortega y Gasset and Brachfeld, the level of this feeling gives rise to inferiority feelings. Thus, the nature of a particular society will depend on the way its members value themselves.